Implementasi Pelayanan Publik Perpajakan Dalam Mendukung Kepatuhan Administratif Wajib Pajak UMKM (Studi Kasus UMKM Pia Kren Gorontalo) - Hanasi, Raihan A.; Korompot, Refais Andrean; Gobel, Verawati Van; Pahrun, Rizka Nurrahma (JPS: Journal of Publicness Studies, 2026)
This study aims to analyze the implementation of public tax services in supporting the administrative compliance of MSME taxpayers at PIA KREN MSME in Gorontalo. The main problems in this study are related to limited understanding of tax administration, insufficient business capital, unorganized turnover recording, and the suboptimal use of digital tax services. This study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation. The findings show that public tax services play an important role in improving the understanding and administrative compliance of MSME actors. However, the implementation still faces several obstacles, including limited capital, weak business administration records, and lack of understanding of tax procedures. In addition, product innovation, digital marketing strategies, and consumer interest are important factors supporting business sustainability. This study concludes that simple, educational, and sustainable tax services can effectively improve the administrative compliance of MSMEs.